Assessing the robustness of multidecadal variability in Northern Hemisphere wintertime seasonal forecast skill. (15th September 2020) - O'Reilly, Christopher H.; Weisheimer, Antje; MacLeod, David; Befort, Daniel J.; Palmer, Tim
Abstract: Recent studies have found evidence of multidecadal variability in Northern Hemisphere wintertime seasonal forecast skill. Here we assess the robustness of this finding by extending the analysis to a diverse set of ensemble atmospheric model simulations. These simulations differ in either the numerical model or type of initialisation and include atmospheric model experiments initialised with reanalysis data and free‐running atmospheric model ensembles. All ensembles are forced with observed sea‐surface temperatures (SSTs) and sea‐ice boundary conditions. Analysis of large‐scale Northern Hemisphere circulation indices over the Northern Hemisphere (namely the North Atlantic Oscillation, the Pacific/North American pattern and the Arctic Oscillation) reveals that in all ensembles there is larger correlation skill in late‐century periods than in mid‐century periods. Similar multidecadal variability in skill is found in a measure of total skill integrated over the whole extratropical region. Most of the differences in large‐scale circulation skill between the skilful late period (as well as the early period) and the less skilful mid‐century period seem to be due to a reduction in skill over the North Pacific and a disappearance of skill over North America and the North Atlantic. The results are robust across different models and different types of initialisation, indicating that the multidecadal variability in Northern Hemisphere winter skill is a robust feature of twentieth‐century climate variability. Multidecadal variability in skill therefore arises from the evolution of the observed SSTs, likely related to a weakened influence of the El Niño–Southern Oscillation on the predictable extratropical circulation signal during the middle of the twentieth century, and is evident in the signal‐to‐noise ratio of the different ensembles, particularly the larger ensembles. Abstract : The Arctic Oscillation ensemble mean correlation skill over moving 30‐year windows, shown for six different ensemble datasets. The red shading shows the 5–95% uncertainty range for the ASF‐20C dataset based on a random bootstrap resampling over the years in each sample (performed 10, 000 times). All datasets show a clear drop in predictability during the mid‐century period.